Clinicopathological study of benign ovarian tumuors - Vohra, Nikita V.; Jokhi, Cyrus Dara; Kanetkar, Sujata R. (International Journal of Research in Medical Sciences, 2018)
Background: The incidence of ovarian tumor amongst gynecological admissions have been reported to vary from 1-3 %. About 75% of these tumors have been found to be benign. Ovarian malignancies represent the greatest clinical challenge of all the gynecological malignancies. During the reproductive years most of the ovarian tumors encountered are benign. About 2/3 of the ovarian tumors are encountered in this group only. The chance that an ovarian tumor is malignant in a patient younger than 45 years is 1 in 15. The differentiation of the benign from malignant tumors can go wrong even with imaging modalities.CA125 along with ultrasound are useful in differentiating benign from malignant tumors. Histopathological examination is gold standard for diagnosis of ovarian neoplasm. Methods: The present study includes consecutive cases of histopathologically proven ovarian tumors of 3 years from June 2010 to May 2013 reported by the Department of Pathology of our tertiary care center. It includes total 150 cases. After careful study of gross findings, appropriate bits were taken from received ovarian specimen, followed by routine paraffin processing to make H and E stained slides. Special stains were used wherever needed. Results: Majority of the cases 91 (60.67%) were benign, 53 (35.33%) were malignant and 6 (4.0%) were borderline. Surface epithelial tumours were the most common type (68.13%) of ovarian neoplasm in this study. Most of tumours in our study occurred in the age group of 21-40 years. Mucinous cystadenomas were most common benign surface epithelial tumour and most common benign tumors overall. There were 22 cases of benign germ cell tumor, all were mature teratoma. All the sex-cord stromal tumours were diagnosed in women older than 40 years. Most common benign lesion in our study is surface epithelial tumour and in age group of 21-40 years. 84% patients studied had symptoms at presentation, out of which 26% of patient presented with dull/dragging pain. Pan hysterectomy was the most common procedure for surgical management. Conclusions: Most of ovarian neoplasm are benign with mucinous cystadenoma being commonest entity. Commonest age group is 21-40 years. Commonest benign germ cell tumor is Mature cystic teratoma. Commonest clinical symptom is dull/dragging pain. Pan hysterectomy was the most common procedure for surgical management.